2008
DOI: 10.1111/j.1540-8167.2008.01231.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Intraatrial Reentrant Tachycardias by Remote Magnetic Navigation in Patients with d‐Transposition of the Great Arteries After Mustard or Senning Procedure

Abstract: Precise mapping of IART in the complex anatomical structures after an atrial switch procedure was feasible and safe using RMN. The maneuverability of the catheter was possible even with a retrograde access crossing two valves. Further reduction of procedural and fluoroscopy times for both patients and physicians seems possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 23 publications
0
26
0
1
Order By: Relevance
“…The reluctance to use an 8-mm solid tip for multiple high-energy application on the systemic side was shared by other groups in similar patient cohorts. 13 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The reluctance to use an 8-mm solid tip for multiple high-energy application on the systemic side was shared by other groups in similar patient cohorts. 13 …”
Section: Discussionmentioning
confidence: 99%
“…The floppy distal end of the magnetic catheter allows free alignment of the embedded magnets in the outer magnetic field, so there is virtually no risk of perforation. 13 The versatility of the magnetic catheter compensates even in situations such as total femoral venous occlusion (patient 7 in group A). Third, appropriate energy delivery at the critical site is the essential step of each ablation procedure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 Currently, further technological advances, such as irrigated catheter system and remote magnetic navigation (RMN) systems, are beginning to provide further solutions for the various remaining problems encountered during electrophysiological studies in adult patients with CHD. [7][8][9] The main advantages of RMN, often used in conjunction with 3D-image integration, namely catheter maneuverability, stability, and precise delineation of the extracardiac and intracardiac anatomy can now be offered in particular situations, such as patients with limited access and mapping difficulty. 10 Previous studies have shown that acute and long-term ablation success rates decline with increasing complexity of the underlying anomaly, 5,11 which seems self-evident when the whole spectrum of adult CHD is considered.…”
mentioning
confidence: 99%